Communicating emergency preparedness practical strategies for the public and private sectors - Coppola, Damon P.; Maloney, Erin K. (Boca Raton, Florida CRC Press, 2017)
"This fully revised edition of Communicating Emergency Preparedness: Practical Strategies for the Public and Private Sectors includes timely case studies, events, and references to articles and opinions about the direction of emergency preparedness communication. The authors draw upon their professional endeavors to inject a new sense of practicality to the text. New images displaying emergency preparedness campaigns are used to further illustrate the materials being presented. For instructors and practitioners alike, this book continues to provide the how-to instruction that is often required, and will only improve upon the success of the first edition in doing so"--Provided by publisher.
Individual preparedness: in theory and in practice. -- Managing risk, emergencies, and disasters. -- The campaign-step 1: early planning. -- step 2: develop a campaign strategy. -- Campaign implementation and evaluation. -- Program support. -- Emergency management public education case studies.
Includes bibliographical references and index.
Keywords: Emergency management; Communication in crisis management; Preparedness